Genome-wide identification, phylogeny and expressional profiles of mitogen activated protein kinase kinase kinase (MAPKKK) gene family in bread wheat (Triticum aestivum L.). (December 2016) - Wang, Meng; Yue, Hong; Feng, Kewei; Deng, Pingchuan; Song, Weining; Nie, Xiaojun
Abstract Background Mitogen-activated protein kinase kinase kinases (MAPKKKs) are the important components of MAPK cascades, which play the crucial role in plant growth and development as well as in response to diverse stresses. Although this family has been systematically studied in many plant species, little is known about MAPKKK genes in wheat (Triticum aestivum L.), especially those involved in the regulatory network of stress processes. Results In this study, we identified 155 wheat MAPKKK genes through a genome-wide search method based on the latest available wheat genome information, of which 29 belonged to MEKK, 11 to ZIK and 115 to Raf subfamily, respectively. Then, chromosome localization, gene structure and conserved protein motifs and phylogenetic relationship as well as regulatory network of these TaMAPKKKs were systematically investigated and results supported the prediction. Furthermore, a total of 11 homologous groups between A, B and D sub-genome and 24 duplication pairs among them were detected, which contributed to the expansion of wheat MAPKKK gene family. Finally, the expression profiles of these MAPKKKs during development and under different abiotic stresses were investigated using the RNA-seq data. Additionally, 10 tissue-specific and 4 salt-responsive TaMAPKKK genes were selected to validate their expression level through qRT-PCR analysis. Conclusions This study for the first time reported the genome organization, evolutionary features and expression profiles of the wheat MAPKKK gene family, which laid the foundation for further functional analysis of wheat MAPKKK genes, and contributed to better understanding the roles and regulatory mechanism of MAPKKKs in wheat.